1995
DOI: 10.1002/bjs.1800820939
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous cholecystostomy: A valuable technique in high-risk patients with presumed acute cholecystitis

Abstract: Percutaneous cholecystostomy offers a potentially important therapeutic modality for critically ill patients with acute cholecystitis who represent a high risk for general anaesthesia. The aim of the study was to assess experience with percutaneous cholecystostomy in resolving the acute episode of cholecystitis without operative intervention. Twenty-two consecutive patients with a clinical diagnosis of acute cholecystitis underwent the procedure. All were at high risk for general anaesthesia, and all but one d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
71
2
4

Year Published

1999
1999
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(86 citation statements)
references
References 26 publications
6
71
2
4
Order By: Relevance
“…One patient underwent cholecystectomy 1 month later, but the other three patients, who were asymptomatic, refused cholecystectomy despite the physician's recommendation. In another report, PTGBD was performed in 21 acute cholecystitis patients with general anesthesia risk [116]. Three patients died of sepsis within 48 h without any appreciable improvement.…”
Section: Commentarymentioning
confidence: 99%
“…One patient underwent cholecystectomy 1 month later, but the other three patients, who were asymptomatic, refused cholecystectomy despite the physician's recommendation. In another report, PTGBD was performed in 21 acute cholecystitis patients with general anesthesia risk [116]. Three patients died of sepsis within 48 h without any appreciable improvement.…”
Section: Commentarymentioning
confidence: 99%
“…We had only one leak that resulted in a worsened septic state and urgent cholecystectomy, something also experienced by others [20]. Our experience of significantly more leaks in case of cystic duct obstruction demonstrated at cholangiography may be worthy of notice, but was not observed by Borzellino et al [23]who observed a 5% obstruction rate.…”
Section: Discussionmentioning
confidence: 36%
“…An established leak or catheter dislodgement can be treated by catheter withdrawal or placement of another catheter, usually without dire consequences [19, 20]. We had only one leak that resulted in a worsened septic state and urgent cholecystectomy, something also experienced by others [20].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations